"Abusing Addiction": Our Language Still Isn't Good Enough. Issue 2 (3rd April 2019) - Ashford, Robert D.; Brown, Austin M.; Curtis, Brenda
ABSTRACT: Previous research has found initial evidence that word choice affects the perception and treatment of those with behavioral health disorders. These previous studies have relied on vignette-based methodologies, however, and a more quantifiable index of the stigma words can produce is needed. The current study uses the Go/No-Go Association Task to calculate a d-prime (sensitivity) indexed score of automatic attitudes to two terms, substance abuser and person with substance use disorder. Participants have significantly more negative automatic attitudes toward the term substance abuser, as compared to person with a substance use disorder. Consistent with previous research, implicit bias does exist for terms commonly used in the behavioral health field. Substance abuser and its derivatives should not be used in professional or lay settings.